Taming the Carboxyl Group for Directed Carbometalation: Observations on the Use of Anions, Dianions and Ester Enolates. Issue 29 (24th June 2014) - Desrat, Sandy; Gray, Philip J.; Penny, Matthew R.; Motherwell, William B.
Abstract Carboxylate anions, dianions and ester enolates provide simultaneous protection and activation for directed carbometalation reactions. Advantage can be taken of the bis‐carbanionic character of the intermediate for further controlled CC bond forming reactions.